2018
DOI: 10.31737/2221-2264-2018-37-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital as a Factor of Sport Achievements: The Case of National Football Teams

Abstract: Социальный капитал -фактор спортивных достижений (на примере национальных сборных по футболу)Аннотация. Социальный капитал имеет важное экономическое значе-ние. Настоящее исследование направлено на определение характера и получе-ние количественных оценок степени влияния социального капитала на результа-тивность командных действий на примере национальных сборных по футболу. Для измерения социального капитала игроков футбольных сборных исполь-зуются национальные индикаторы, построенные на основе опроса European … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The history of football participation is a time dimension that captures the development of football in a country and has the advantage of being easily measured and readily available empirically [ 25 , 43 ]. chose the year of participation in the first international football match (by country) as a proxy variable for international football history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The history of football participation is a time dimension that captures the development of football in a country and has the advantage of being easily measured and readily available empirically [ 25 , 43 ]. chose the year of participation in the first international football match (by country) as a proxy variable for international football history.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is also found in the case of the Olympic Games, especially in developing countries. [ 43 ] similarly showed that population size is an exception, as it is not crucial for the estimation of the market value of the national team.
Fig.
…”
Section: Discussionmentioning
confidence: 99%